WEBVTT
00:00:01.460 --> 00:00:04.790
Simplify 𝑥 cubed all squared.
00:00:06.300 --> 00:00:09.870
The first thing to consider here is what we mean by squared.
00:00:10.370 --> 00:00:15.360
Squaring a number or expression means multiplying it by itself.
00:00:16.720 --> 00:00:23.360
Therefore, 𝑥 cubed squared means 𝑥 cubed multiplied by 𝑥 cubed.
00:00:24.540 --> 00:00:36.520
In order to simplify this, we need to consider one of the laws of indices: 𝑥 to the power of 𝑎 multiplied by 𝑥 to the power of 𝑏 is equal to 𝑥 to the power of 𝑎 plus 𝑏.
00:00:37.400 --> 00:00:41.450
When we are multiplying, we can add the exponents or indices.
00:00:42.640 --> 00:00:45.660
Adding three and three gives us an answer of six.
00:00:46.070 --> 00:00:51.680
Therefore, 𝑥 cubed all squared is equal to 𝑥 to the power of six.
00:00:52.950 --> 00:00:56.130
This leads us to a quicker method to solve the initial problem.
00:00:56.660 --> 00:01:06.920
One of the other laws of indices states that 𝑥 to the power of 𝑎 to the power of 𝑏 is equal to 𝑥 to the power of 𝑎 multiplied by 𝑏.
00:01:08.210 --> 00:01:16.450
In our example, this means that we can rewrite 𝑥 cubed all squared as 𝑥 to the power of three times two.
00:01:17.730 --> 00:01:20.440
Three multiplied by two is equal to six.
00:01:20.790 --> 00:01:24.080
Therefore, our answer is 𝑥 to the power of six.